Crystal Structure and Hirshfeld Surface Analysis of Hexakis(acetoxymethyl)benzene - Manuel Stapf; Wilhelm Seichter; Monika Mazik (Molbank, 2025)
Representatives of the hexasubstituted benzene derivatives, also known as hexa-hosts, have been the subject of extensive studies in solution and in the solid state, including the investigation of their ability to act as artificial receptors for various substrates, as well as detailed conformational analyses. In this paper, we describe the X-ray crystal structure of hexakis(acetoxymethyl)benzene (1), a member of the above class of compounds. The molecules of 1 adopt an aaabbb conformation, in which three side-arms point to the same face of the central benzene ring, while the other three point in the opposite direction. As the compound lacks strong hydrogen bond donors, C–H···O hydrogen bonds connect the molecules to a three-dimensional supramolecular network. According to the Hirshfeld surface analysis, the H∙∙∙O/O∙∙∙H interactions represent the major contribution of the molecular Hirshfeld surface.